Aluminum Composite Cutting Machine Development Using CNC - อัศวกุลชัย, สุวรรณี (Srinakharinwirot University Engineering Journal, 2018)
The main objective of this study is to design and develop an Aluminum Composite (AC) cutting machine using computer numerical control (CNC) that is more efficient than the circle saw. Since most of the small manufacturing enterprises (SMEs) in Thailand still use circle saws in general. In this study, the machine is 1.10 x 1.45 x 0.78 meter and the working space is 0.89 x 1.23 meter. The innovation of this AC cutting machine is the trimming router bit. The machine is automatically controlled using Program Mach 3 as a tool to run microprocessor 5 axis breakout board via pararell port. In addition, the cutting AC pattern is designed by using JDPaint and Artcam. Therefore, this study is to compare the efficiency of the AC cutting machine between the machine and the circular saw. The results from this study demonstrates that the machine works more efficiently as follows: less time consuming 50.66%, more accuracy 2.08%, less waste during production 26.75%, less aluminium distribution 72.72%, more safety that the accident less than 65.58% and less noise pollution 17.53%. It can be concluded that the Aluminum Composite (AC) cutting machine using computer numerical control is good for Thai SMEs and the cost is less than the import 60.48%. Moreover, the machine is made in Thailand that is easy for after sale service and maintenance. The machine is still in the examine process before announcement for patent in Thailand with number 1703000038 on January 10, 2017.